2015
DOI: 10.1002/clc.22419
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Myocardial Ischemia in Patients With Coronary Artery Disease and Obstructive Sleep Apnea: Effect of Continuous Positive Airway Pressure Therapy

Abstract: Background: Obstructive sleep apnea (OSA) is associated with an increased risk of cardiovascular complications. OSA and coronary artery disease (CAD) share the same risk factors and coexist in many patients. In previous studies, repeated nocturnal cardiac ischemic events in OSA patients with CAD have been reported. Hypothesis: We hypothesized that OSA may precipitate myocardial ischemia, evidenced by ST-segment depression and elevated N-terminal brain natriuretic peptide (NT-proBNP) and high-sensitivity tropon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…In a small study of 21 patients with severe OSA and presence of CAD, Valo and colleagues found that levels of hs-cTnT drawn before and after sleep were not affected by one night of CPAP use [135]. Further, in this study, electrocardiogram monitoring of ST segments were conducted throughout the night of sleep to document any evidence of myocardial ischemia [135].…”
Section: The Role Of Pap Therapy and Troponinsmentioning
confidence: 79%
See 4 more Smart Citations
“…In a small study of 21 patients with severe OSA and presence of CAD, Valo and colleagues found that levels of hs-cTnT drawn before and after sleep were not affected by one night of CPAP use [135]. Further, in this study, electrocardiogram monitoring of ST segments were conducted throughout the night of sleep to document any evidence of myocardial ischemia [135].…”
Section: The Role Of Pap Therapy and Troponinsmentioning
confidence: 79%
“…Further, in this study, electrocardiogram monitoring of ST segments were conducted throughout the night of sleep to document any evidence of myocardial ischemia [135]. Although use of CPAP reduced ST segment depression during the lowest point of oxygen desaturation with sleep, this finding was not significant.…”
Section: The Role Of Pap Therapy and Troponinsmentioning
confidence: 88%
See 3 more Smart Citations